Xerogenic medications may contribute to decreased unstimulated salivary flow in patients with oral burning and/or gastro-esophageal reflux disease - Sangalli, Linda; Eldomiaty, Walied; Miller, Craig S. (Frontiers in Dental Medicine, 2023)
Background. Patients who complain of mucosal burning sensations (i.e., glossodynia and gastro-esophageal reflux disease, GERD) often take multiple medications. However, the relationship between xerogenic medication intake and salivary flow in these patients has not been thoroughly examined. Methods. A retrospective study of 192 consecutive patients diagnosed with glossodynia (ICD-10-CM) at a regional center over a six-year period was performed. Data from electronic health records were extracted and relationships between medication intake, unstimulated whole salivary flow rate (UWSFR), xerostomia and GERD were determined by chi-square, t-test, and correlation analysis. Results. Of 134 records that met inclusion criteria, 87.1% of patients reported daily intake of one or more xerogenic medications. Two or more xerogenic medications were taken significantly more often by patients with glossodynia reporting GERD than those with glossodynia without GERD (p=.02). UWSFR was negatively correlated with number of medications (r(103)=-.277, p=.005) and xerogenic medications (r(103)=-.195, p=.049). The lowest UWSFR was observed with use of trazodone and cyclobenzaprine. Conclusions. Daily xerogenic medication intake, hyposalivation, and xerostomia were commonly present and potentially interrelated in patients who suffer from glossodynia and/or GERD. Practical Implications. Clinicians should be aware of the consequences of prescribing multiple and certain xerogenic medications in reducing UWSFR, especially in patients physiologically at risk of hyposalivation such as those suffering from GERD and/or glossodynia.